Analysis of ectopic pregnancy in a tertiary care hospital - N., Sunanda; M., Impana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Ectopic pregnancy is a life threatening obstetrics emergency in early trimester associated with increased risk of morbidity and mortality if not timely intervened. High index of clinical suspicion is required for early diagnosis specially in reproductive age group women presenting with history of amenorrhea. Aim was to analyse the incidence of ectopic pregnancy, its risk factors, clinical presentation and management of ectopic pregnancy. Methods: A retrospective observational study was conducted on ectopic pregnancy cases admitted in a tertiary care institute over a period of 5 years from January 2018 to December 2022. A total of 221 cases of ectopic pregnancy were analysed for parameters like age, parity, gestational age, clinical presentation, risk factors, intervention and outcome. Results: There were 221 ectopic pregnancy cases during the study period with incidence of 4.3/1000 deliveries. The mean age was 24 years with the mean gestational age of 6.83±1.25 weeks. The commonest risk factor identified was any previous pelvic surgeries (49.32%), PID (11.76%), history of abortion and use of IUCD (8.14%). The triad of ectopic pregnancy (pain abdomen, history of amenorrhoea, bleeding PV) was found in 35.29%. Ectopic pregnancy was ruptured in 148 cases (66.96%) and unruptured in 73 cases (33.03%). Majority of the ectopic pregnancy was tubal ectopic and most common site was Ampulla (47.06%) followed by isthmus (23.98%). 96% of the cases were managed by surgical intervention and two maternal deaths were found during the study period. Conclusions: Proper evaluation of risk factors9and early diagnosis will help in preserving fertility and also reducing8morbidity and mortality. Majority of the cases were in ruptured condition, rendering8conservative management was impossible. Therefore awareness of its determinants can aid in8early detection of more number of such cases8in unruptured condition especially in8peripheral center, leading to early referral.